Effective methods for software testing - Perry, William E. (Wiley, 2000)
Testing even a simple system can quickly turn into a potentially infinite task. Faced with tight costs and schedules, testers need to have a toolkit of practical techniques combined with hands-on experience and the right strategies in order to complete a successful project